An epidemic within a pandemic of women, children and domestic violence: A case of Zimbabwe from 2020-2021 - Joseph Muwanzi (MSU Press, 2023)
The current global Covid-19 pandemic has not spared Zimbabwe from the impact of domestic violence against women and girls. To curtail the spread of the covid-19 virus, the government of Zimbabwe enforced restrictions on movements causing an epidemic of gender-based violence. The trend became ‘an epidemic within a pandemic’ against women and children. Emerging evidence reflects that lockdown affected economic growth and increased poverty, caused inability for women to es- cape from abusive partners; ineffective health, and law enforcement service delivery. As a result, unequal gender relations, and patriarchal norms against women became prominent. Identified forms of domestic violence are physical, sexual, economic and psychological abuse leading to deaths, injuries, commercial sex work, stress, early marriages, and unwanted pregnancies; child labour and sexually transmitted infec- tions. The study identified government, church, policy-makers and non-governmental organisations, donors and women’s organizations as institutions with possible solu- tions. The study argues that the domestic violence epidemic has exposed, and been exacerbated by the Covid-19 pandemic, hence multifaceted intervention strategies are needed to safeguard vulnerable groups. Strategies comprise of psychosocial sup- port, use of social media to disclose domestic violence, effective legal and justice system operations, inclusivity in policy-making, and implementation process, eco- nomic empowerment for income generating projects, and provision of an effective health delivery system. Complexities which hinder effective intervention against do- mestic violence were also identified. Hence, the study recommends that stakeholders to ensure that necessary services remain accessible. Also, adequate funding to enable high quality of domestic violence interventions, prioritise prevention, response and risk mitigation activities as part of stakeholders’ objectives in humanitarian pro- grams and inclusivity of women, and girls in policy-making, and implementation. The study adopts a qualitative approach. Under current lockdown conditions, desk review, official and media reports analysis on the topic; WhatsApp interviews with key selected informants were used.